1997
DOI: 10.1002/(sici)1097-4652(199711)173:2<288::aid-jcp38>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Gene rearrangements in the molecular pathogenesis of acute promyelocytic leukemia

Abstract: Acute Promyelocytic Leukemia (APL) is a distinct subtype of myeloid leukemia that in the USA alone affects more than 3,000 individuals every year. APL is characterized by three distinct and unique features: i) the accumulation in the bone marrow of tumor cells with promyelocytic features; ii) the invariable association with specific translocations which always involve chromosome 17 and the Retinoic Acid Receptor alpha (RAR alpha) locus; iii) the exquisite sensitivity of APL blasts to the differentiating action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 80 publications
2
22
0
Order By: Relevance
“…Recent work by Shibakura et al 28 showed that the downregulation effect of ATRA on TF mRNA in NB4 cells was mediated via both RAR␣ and RAR␤ nuclear receptors, and it may imply that the existence of unique fusion protein PML-RAR␣ probably involves the aberrant expression of TF in NB4 cells through its welldemonstrated dominant negative effects on wild-type RAR␣, 35 as supported by our result ( Figure 5). The practical mechanism may also involve the AP-1 sites located within the −172 to −227 region of TF gene, which have been shown to mediate the LPS-induced TF expression in THP-1 cells, 36 for Vallian et al 37 recently reported that both PML and PML-RAR␣ enhanced the AP-1-mediated transcription activity and this modulation by PML-RAR␣, but not PML, was abrogated by addition of ATRA.…”
Section: Figuresupporting
confidence: 86%
“…Recent work by Shibakura et al 28 showed that the downregulation effect of ATRA on TF mRNA in NB4 cells was mediated via both RAR␣ and RAR␤ nuclear receptors, and it may imply that the existence of unique fusion protein PML-RAR␣ probably involves the aberrant expression of TF in NB4 cells through its welldemonstrated dominant negative effects on wild-type RAR␣, 35 as supported by our result ( Figure 5). The practical mechanism may also involve the AP-1 sites located within the −172 to −227 region of TF gene, which have been shown to mediate the LPS-induced TF expression in THP-1 cells, 36 for Vallian et al 37 recently reported that both PML and PML-RAR␣ enhanced the AP-1-mediated transcription activity and this modulation by PML-RAR␣, but not PML, was abrogated by addition of ATRA.…”
Section: Figuresupporting
confidence: 86%
“…APL, M3 subtype of acute myeloid leukemia (AML), accounts for more than 10% of all AMLs and is characterized by three distinctive and unique features (reviewed in Warrell et al, 1993b;Grignani et al, 1994;Pandol®, 1996;Kalantry et al, 1997;Melnick and Licht, 1999): (1) the accumulation in the bone marrow of tumor cells with promyelocytic features; (2) the invariable association with speci®c translocations which always involve chromosome 17; and (3) the exquisite sensitivity of APL blasts to the dierentiating action of retinoic acid (RA). From this point of view APL has become the paradigm for therapeutic approaches utilizing dierentiating agents.…”
Section: Introductionmentioning
confidence: 99%
“…However, although eective, treatment with RA alone in APL-1 patients induces disease remission transiently and relapse is inevitable if remission is not consolidated with chemotherapy. In addition, in the majority of cases, relapse is accompanied by RA resistance (Warrell et al, 1993b;Grignani et al, 1994;Pandol®, 1996;Kalantry et al, 1997;Melnick and Licht, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Certain forms of acute promyelocytic leukemia (APL) are associated to chromosome translocations involving RARα gene, and PML (Promyelocytic leukemia, t(15;17)) or PLZF (Promyelocytic leukemia zinc finger, t(11;17)), leading to the fusion proteins PML/RARα and PLZF/RARα, respectively (reviewed in ref. 34). The mechanism employed by these fusion proteins involves HDAC recruitment on target genes; this recruitment results probably in the repression of transcription of these genes, and as a consequence it inhibits cell response to retinoic acid, blocking haematopoietic terminal differentiation and leading to increased proliferation.…”
Section: Acute Myelogenous Leukemia (Aml)mentioning
confidence: 99%